Effects of Aloe vera against radiation induced hepatic alterations in swiss albino mice - PRIYANKA DADUPANTHI (International Journal of Pharma and Bio Sciences, 2018)
Nowadays uses of radiation and radioisotopes have increased many folds in the fields of radio diagnosis, radiotherapy, industries, agriculture, nuclear research etc. By using some agents diagnostic and therapeutic use of radiation is of prime importance and their effects especially on liver and other systems have attracted the interest to minimize them. Considering this state of affairs, the present study was planned to evaluate the protective effect of Aloe vera (a herbal drug) against radiation induced histopathological alterations in the liver of Swiss albino mice. The animals were exposed to 5.5 Gy of gamma rays with or without treatment. The Aloe vera was administered since 15 days prior to irradiation treatment. The animals from all the experimental groups were abdicated by cervical dislocation at each post-treatment interval of ¼, 1, 3, 5, 10 and 20 days. After abdicated the animals, pieces of the liver were cut and immediately fixed in Bouin’s fluid for histological observations after routine processing. The changes observed were distortion of hepatic architecture, intracellular oedema, narrower sinusoids, cytoplasmic degranulation, vacuolation, hyperaemia, pycnotic and crenated nuclei. After combined treatment of radiation and aloe additive effects were noted. The Aloe vera pretreated mice showed less severe changes in comparison to the non drug treated animals at all the corresponding intervals. An early and fast recovery was also observed in Aloe vera treated groups. Thus it appears the Aloe vera is potent enough to check radiation induced hepatic lesions in Swiss albino mice.